Whale falls as chemosynthetic refugia: a perspective from free-living deep-sea nematodes - Avila, Ana K. F.; Shimabukuro, Maurício; Couto, Daniel M.; Alfaro-Lucas, Joan M.; Sumida, Paulo Y. G.; Gallucci, Fabiane (Frontiers in Marine Science, 2023)
Whale carcasses create habitats in the deep sea which are colonized by organisms related to other chemosynthetic environments suggesting that whale falls may act as ‘stepping-stones’ for the dispersal and evolution of deep-sea organisms. Such evidence comes mainly from macrofaunal organisms whereas for the smaller meiofauna, data on whalebone assemblages is lacking. In this study, we investigated nematode colonization of whalebones experimentally deployed at 1500 and 3300 m depth and bones from a natural whale carcass found at 4204 m, in the Southwest Atlantic Ocean, off Brazil. By comparing whalebone assemblages to other deep-sea environments, we tested the hypothesis that whale fall nematode assemblages are more similar to those from other cognate chemosynthetic-based habitats, rather than those from sediments surrounding the carcass or other deep-sea habitats. Our results showed that whalebone nematode assemblages resemble those of hydrothermal vents and cold seeps and suggest that the stepping-stone hypothesis may be valid also for the meiofauna. It also showed that oceanographic conditions and the age of the carcasses on the ocean floor could influence nematode assemblage composition and richness. Such findings highlight the importance of organic falls for understanding the connectivity and phylogeny of benthic organisms, including representatives of the meiofauna.